4t-12=6(t=3)

Simple and best practice solution for 4t-12=6(t=3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t-12=6(t=3) equation:



4t-12=6(t=3)
We move all terms to the left:
4t-12-(6(t)=0

You can always share this solution

See similar equations:

| 3x²+2x-33=0 | | (2x+1)+39=190 | | 5n+7=81 | | (p+3)(p+10)=0 | | 15x+12+3x(2x-6)=3x-(21x-1)+2 | | X-50+x+x-70=180 | | X²-7x=20 | | 2.14x-12.18=-576 | | e/3?=7 | | e/?3=7 | | Z+37=z+z-38 | | 2=u3?6 | | 2=u3? 6 | | 8^-2-x=168 | | 75=3j+18 | | 8x+7.5=119.5 | | 7h-h=42 | | 12z+34=4z-38 | | 82?r=28 | | k/9=6? | | 2=51?b | | 6=k/9? | | 25=51?b | | 11+6g=53 | | d3?4=3 | | x/4-12=-18 | | d3? 4=3 | | 18+2h=68 | | 10+7v=59 | | 7(2x-5)=-21 | | 4x-32,8=65,4 | | 7(2x-5=-21 |

Equations solver categories